Protective effects of N-acetylcysteine against irinotecan – induced pulmonary toxicity in female albino rats - Khudhur, Hawrin Burhan; Al-Hassani, Ansam (Zanco Journal of Medical Sciences (ZJMS), 2024)
Background and objective: Idiopathic pulmonary fibrosis (IPF) is a deadly lung illness characterized by progressive lung fibrosis and deteriorating lung function, with the uncertain origin and few therapeutic options. Chemotherapy such as Irinotecan (IRI) is the major antineoplastic agent that produces IPF and induces lung damage. N-acetylcysteine (NAC) has a glutathionepre cursor that protects lung function. The present study was designed to evaluate the protective effects of N-acetylcysteine in Irinotecan induced lung toxicity. Methods: In total, 18 female Albino rats were divided into three groups, aging from 8-12 weeks and weighing between 180-250 g. The control group G1 received 1 ml intraperitoneal (IP) normal saline for 14 days, G2 Irinotecan group was administered a single high dose of Irinotecan (300 mg/kg) intraperitoneal instillation. And G3 N-acetylcysteine group (500 mg/kg/day) orally one week before Irinotecan (300 mg/kg) injection continued to the end of 21 days of the experimental period. Histopathology, cell counts, cytokine responses in the serum (TGF-β, TNF-α, and IL-6), and weight measurements were studied to evaluate the protective effects. Results: Histopathological study indicated the Irinotecan–induced pulmonary fibrosis with a significant increase in the levels of inflammatory cytokines, and the protective impacts of N-acetylcysteine administration attenuated the degree of inflammation and fibrosis with a reduced level of cytokines concentrations in serum. Conclusion: N-acetylcysteine can protect the lungs from both histological alterations and activation of cytokines caused by pulmonary toxicity induced by Irinotecan.